Analisis Efektivitas Analisis Efektivitas Strategi Komunikasi Pemasaran Pasco.lpg dalam Meningkatkan Minat Beli Konsumen - Lestari S, Meidianty; Waskito, Budhi (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2022)
Pasco.lpg is one of the pioneers of ice blends which was founded back in 2019 with the ‘Easy To Operate’ concept. Targeting a market niche where there is too much coffee on the market, using non-coffee variants as a market gap by relying on their marketing techniques as a shield. Slightly decreased due to the Covid-19 pandemic, Pasco.lpg utilizes social media as a medium for promotion and continues to conduct online sales activities. Technological and the internet as it is today is useful and helps sales activities of Pasco.lpg. So this study aims to determine as well as analyze the effectiveness of the marketing communication strategy carried out by Paco.lpg. This research uses descriptive qualitative method. And also uses data collection such as obsevation, interviews to documentation. The results show the effectiveness is running well with Pasco.lpg sales in 2021 increasing more than the previous year.